When ‘Messiahs’ turn ‘Persecutors’ : reflecting on the blocked transition of liberation movements in Africa - case study of ZANU-PF - Cistac, Gilles (University of Pretoria, 2010)
A Dissertation submitted to the Faculty of Law University of Pretoria, in partial fulfilment of the requirements for the degree Masters of Law (LLM in Human Rights and Democratisation in Africa). Prepared under the supervision of Gilles Cistac, Faculty of Law, Universidade Eduardo Modlande, Maputo, Mocambique.